Transmission of hepatitis C virus infection among younger and older people who inject drugs in Vancouver, Canada. - Jacka, B; Applegate, T; Poon, A; Raghwani, J; Harrigan, P; DeBeck, K; Milloy, M; Krajden, M; Olmstead, A; Joy, J; Marshall, B; Hayashi, K; et al. (Elsevier, 2016)
Background and Aims Understanding HCV transmission among people who inject drugs (PWID) is important for designing prevention strategies. This study aimed to investigate whether HCV infection among younger injectors occurs as a result of few or many transmission events from older injectors to younger injectorsamong PWID in cohorts recruited in Vancouver, Canada. Methods HCV antibody positive participants at enrolment or follow-up (1996-2012) were tested for HCV RNA and sequenced (Core-E2). Time-stamped phylogenetic trees were inferred using BEAST. Association of age with phylogeny was testedusing statistics implemented in the software BaTS. Factors associated with clustering (maximum cluster age: five years) were identified using logistic regression. Results Among 655 participants with HCV subtype 1a, 2b and 3a infection (26% female, 23% HIV+): 22% were younger (<27 years), and 11% had recent HCV seroconversion. When inferred cluster age was limited to <5 years, 15% (n=100) were in clusters/pairs.Although a moderate degree of segregation was observed between younger and older participants, there was alsotransmission between age groups. Younger age (<27 vs. >40, AOR: 3.01, 95% CI: 1.44, 6.29) and HIV infection (AOR: 1.73, 95%-CI: 1.06, 2.83) were independently associated with clustering. Conclusions In this population of PWID from Vancouver, HCV infection among young injectors was seeded from many transmission events between HCV-infected older injectors and younger injectors.Phylogenetic clustering was associated with younger age and HIV co-infection. These data suggest that HCV transmission among PWID is complex, with transmission occurring between and among older and younger PWID.